Transcriptomic Analysis of Breast Cancer Stem Cells and Development of a pALDH1A1:mNeptune Reporter System for Live Tracking. Issue 21 (8th September 2019) - Bidan, Nadège; Bailleul‐Dubois, Justine; Duval, Jérémy; Winter, Marie; Denoulet, Marie; Hannebicque, Karine; El‐Sayed, Ihsan Y.; Ginestier, Christophe; Forissier, Violaine; Charafe‐Jauffret, Emmanuelle; Macario, Manon; Matsunaga, Yukiko T; et al.
Abstract: Many solid cancers are hierarchically organized with a small number of cancer stem cells (CSCs) able to regrow a tumor, while their progeny lacks this feature. Breast CSC is known to contribute to therapy resistance. The study of those cells is usually based on their cell‐surface markers like CD44 high /CD24 low/neg or their aldehyde dehydrogenase (ALDH) activity. However, these markers cannot be used to track the dynamics of CSC. Here, a transcriptomic analysis is performed to identify segregating gene expression in CSCs and non‐CSCs, sorted by Aldefluor assay. It is observed that among ALDH‐associated genes, only ALDH1A1 isoform is increased in CSCs. A CSC reporter system is then developed by using a far red‐fluorescent protein (mNeptune) under the control of ALDH1A1 promoter. mNeptune‐positive cells exhibit higher sphere‐forming capacity, tumor formation, and increased resistance to anticancer therapies. These results indicate that the reporter identifies cells with stemness characteristics. Moreover, live tracking of cells in a microfluidic system reveals a higher extravasation potential of CSCs. Live tracking of non‐CSCs under irradiation treatment show, for the first time, live reprogramming of non‐CSCs into CSCs. Therefore, the reporter will allow for cell tracking to better understand the implication of CSCs in breast cancer development and recurrence.